Development Of Ac Voltage Controller For Energy Saving Of Induction Motor - Ahmad, Zainab (2002)
Energy saving can be defined as the ability to reduce the electricity consumption when using an electrical machine. The most common electrical machine is the induction motor. Although it is the workhorse of the industry because of its ruggedness, low cost, low maintenance and versatility, it suffers from considerable inefficiencies and losses. The induction motor operates most efficiently at full load. However, in many instances, it runs on full load for only part of the time. At light loads, induction motors are approximately inductive and have poor power factor. This leads to high power consumption, thus reduces the motor efficiency.Modulating the power flow from the supply to the load is the task of a power controller. This thesis presents the power controller called the pulse width modulated (PWM) ac chopper voltage controller. The PWM and chopping technique is predominantly used in dc applications. However, in this thesis, these two techniques will be implemented for the ac application. AC voltage controller is a single stage power converter that enables voltage variation by varying the duty cycle of its switching devices. Reduction in voltage can be made to suit the power demand of induction motor running at light loads. The advantages of this voltage controller includes: elimination of lower-order harmonics, improvement of input power factor, nearly sinusoidal input and output current and voltage waveforms, better transient response due to soft-starting and reduced number of control switches. This voltage controller was simulated using the Pspice software and then assembled in the laboratory. A good agreement has been obtained between the simulation results and the experimental results.